2022
DOI: 10.1007/s40801-022-00339-x
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 Substrate Dispensing Among Patients Dispensed Mirabegron: An Administrative Claims Analysis

Abstract: Background Overactive bladder (OAB) is characterized by the presence of bothersome urinary symptoms. Pharmacologic treatment options for OAB include anticholinergics and β 3 -adrenergic agonists. Use of β 3 -adrenergic agonists may result in similar treatment efficacy with a decreased side effect profile compared with anticholinergics because high anticholinergic burden is associated with cardiovascular and neurologic side effects. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…A previous analysis of dispensing claims has highlighted the high frequency with which CYP2D6 substrates of any kind are codispensed in patients with OAB receiving mirabegron; approximately 70% of patients who received mirabegron also received a CYP2D6 substrate [ 15 ]. Codispensing of ≥ 1 CYP2D6 substrate with mirabegron was associated with patients being older and with having increased healthcare resource utilization, baseline polypharmacy, and comorbidities compared with mirabegron users who did not receive concomitant CYP2D6 substrates [ 15 ]. In an analysis of medication dispensing in long-term care facilities, > 90% of residents who received mirabegron had also received a CYP2D6 substrate during a 5-year analysis window [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous analysis of dispensing claims has highlighted the high frequency with which CYP2D6 substrates of any kind are codispensed in patients with OAB receiving mirabegron; approximately 70% of patients who received mirabegron also received a CYP2D6 substrate [ 15 ]. Codispensing of ≥ 1 CYP2D6 substrate with mirabegron was associated with patients being older and with having increased healthcare resource utilization, baseline polypharmacy, and comorbidities compared with mirabegron users who did not receive concomitant CYP2D6 substrates [ 15 ]. In an analysis of medication dispensing in long-term care facilities, > 90% of residents who received mirabegron had also received a CYP2D6 substrate during a 5-year analysis window [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mirabegron and ten predefined CYP2D6 substrate groups (amitriptyline/nortriptyline, aripiprazole, citalopram/escitalopram, donepezil, duloxetine/venlafaxine, hydrocodone, metoprolol/carvedilol, tamsulosin, tolterodine, and tramadol; Supplementary Table 1 in the electronic supplementary material [ESM]) were identified using National Drug Codes from pharmacy dispensing claims. Selection of CYP2D6 substrates was based on medications most frequently prescribed in the United States as defined previously [ 15 , 16 ], with high susceptibility to CYP2D6 inhibition, and with evidence for exposure-related toxicity that could result in an identifiable adverse effect. Medications were grouped together if they were in the same therapeutic class and were considered therapeutically interchangeable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective analysis of 106,260 commercially insured adult patients who were dispensed mirabegron between January 2011 and December 2019 found that 68.5% had overlapping dispensing with ≥1 CYP2D6 substrates. 9 Among patients ≥65 years of age, 72.1% had CYP2D6 substrate dispensations that overlapped with mirabegron. 9 A separate retrospective analysis of pharmacy claims from 159,785 residents in long-term care facilities who were dispensed OAB medications between May 1, 2013, and May 1, 2018, found that 93% of residents who received mirabegron were dispensed a CYP2D6 substrate during the analysis period.…”
mentioning
confidence: 99%
“…9 Among patients ≥65 years of age, 72.1% had CYP2D6 substrate dispensations that overlapped with mirabegron. 9 A separate retrospective analysis of pharmacy claims from 159,785 residents in long-term care facilities who were dispensed OAB medications between May 1, 2013, and May 1, 2018, found that 93% of residents who received mirabegron were dispensed a CYP2D6 substrate during the analysis period. 10 Owing to study limitations, it is unknown if the CYP2D6 substrate dispensing overlapped with mirabegron dispensing, if residents took both the CYP2D6 substrate and mirabegron concurrently, or if prescribing clinicians made proactive dose adjustments to account for coadministration.…”
mentioning
confidence: 99%